2007
DOI: 10.1111/j.1600-0501.2007.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive and critical review of dental implant prognosis in periodontally compromised partially edentulous patients

Abstract: No statistically significant differences in both short-term and long-term implant survival exist between patients with a history of chronic periodontitis and periodontally healthy individuals. Patients with a history of chronic periodontitis may exhibit significantly greater long-term probing pocket depth, peri-implant marginal bone loss and incidence of peri-implantitis compared with periodontally healthy subjects. Even though the short-term implant prognosis for patients treated for aggressive periodontitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
1
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(195 citation statements)
references
References 48 publications
5
171
1
7
Order By: Relevance
“…Karoussis 22 encontró un diferencia no significativa en la sobrevivencia de implantes entre pacientes no periodontales y pacientes con periodontitis tratada. Sin embargo, sí reportó que pacientes con antecedente de periodontitis tratada presentaban una tasa significativa mayor de aumento de la profundidad de sondaje y de pérdida ósea marginal.…”
Section: Influencia De La Enfermedad Periodontal En La Terapia Implanunclassified
“…Karoussis 22 encontró un diferencia no significativa en la sobrevivencia de implantes entre pacientes no periodontales y pacientes con periodontitis tratada. Sin embargo, sí reportó que pacientes con antecedente de periodontitis tratada presentaban una tasa significativa mayor de aumento de la profundidad de sondaje y de pérdida ósea marginal.…”
Section: Influencia De La Enfermedad Periodontal En La Terapia Implanunclassified
“…Although these bacteria were identified at tooth and implant sites the clinical parameters did not indicate progressive bone loss or implant failure. [24] These distinct differences between the edentulous and partially edentulous groups suggest that the presence of pockets around teeth, which harbor a large variety of bacteria, may serve as a reservoir of periodontal pathogens contributing to contamination of peri-implant sites. The longitudinal success of osseointegrated implants in edentulous patients may be due to a reduced intraoral challenge by implicated periodontal pathogens and, conversely, the presence of such pathogens in partially edentulous patients may conceivably hasten subsequent peri-implant disease if patients are not well maintained.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Karoussis et al 24 reported that patients with a history of periodontitis manifested significantly greater probing depths, more peri-implant marginal bone loss, and a higher incidence of peri-implantitis. Also, implants which display a gap between implant and abutment permits new bacterial colonization.…”
Section: Jaypee Hs Grover Sagrika Shuklamentioning
confidence: 99%